2005
DOI: 10.1107/s0907444905005883
|View full text |Cite
|
Sign up to set email alerts
|

SSEP-2.0: Secondary Structural Elements of Proteins

Abstract: SSEP is a comprehensive resource for accessing information related to the secondary structural elements present in the 25 and 90% non-redundant protein chains. The database contains 1771 protein chains from 1670 protein structures and 6182 protein chains from 5425 protein structures in 25 and 90% non-redundant protein chains, respectively. The current version provides information about the ahelical segments and b-strand fragments of varying lengths. In addition, it also contains the information about 3 10 -hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…As a control for the effect of the pivaloyl group on K trans / cis , we observed that the pivaloyl group minimally affected K trans / cis for AYPN. These data are consistent with a high frequency of Pro at the i position of type VI β‐turns 14, 24, 117, 118. Moreover, these data emphasize the importance of the residue preceding Pro i on cis – trans isomerism of the Xaa i– 1 –Pro i amide bond, in which a cis conformation is stabilized by a favorable interaction between the aromatic ring of Tyr i +1 and H α of the i –1 residue 22, 28–32…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…As a control for the effect of the pivaloyl group on K trans / cis , we observed that the pivaloyl group minimally affected K trans / cis for AYPN. These data are consistent with a high frequency of Pro at the i position of type VI β‐turns 14, 24, 117, 118. Moreover, these data emphasize the importance of the residue preceding Pro i on cis – trans isomerism of the Xaa i– 1 –Pro i amide bond, in which a cis conformation is stabilized by a favorable interaction between the aromatic ring of Tyr i +1 and H α of the i –1 residue 22, 28–32…”
Section: Resultssupporting
confidence: 82%
“…As a starting point, we considered the frequencies of residues in type VI β‐turns. Due to inadequate statistics, analysis of the PDB has revealed only a limited number of trends for type VI β‐turns 14, 24, 117, 118. The most significant residue preferences for type VI β‐turns are (a) absolute conservation of Pro at the i +2 residue, to promote cis amide bonds, and (b) a significant preference for aromatic residues at the i +1 residue.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of the observed ion pairs, the percentage of individual basic and acidic residues involved in ion pair formation was also calculated and these residues were classifi ed based on their geometrical orientations. The knowledgebase SSEP (Balamurugan et al 2005;Shanthi et al 2003) was deployed to get the secondary structural elements and the residues involved in ion pairs were analysed.…”
Section: Methodsmentioning
confidence: 99%
“…CI techniques have been applied to give structural insights and predictions in many stages: From secondary structure prediction [150][151][152][153][154][155][156][157][158][159][160][161][162] to domain identification, [163][164] fold and class predicition, [165][166][167][168][169][170] tertiary structure predicition [171][172][173] and structural characteristics assesment. [174][175][176][177][178] …”
Section: Structure Predictionmentioning
confidence: 99%